O doente terminal - Aspectos Práticos - de Moura, Pereira (1995)
The authors present some reflexions about the terminal patient. ln the First National Meeting of Domicialiry Assistance, this theme was debated, particulary the physical problems; in the nº 8 of "Médice", was essentially debated the psycological aspects, and we think that this two works are complementary.